Progressive muscle loss is an independent predictor for survival in locally advanced oral cavity cancer: A longitudinal study. (May 2021) - Lee, Jie; Liu, Shih-Hua; Chen, John Chun-Hao; Leu, Yi-Shing; Liu, Chung-Ji; Chen, Yu-Jen
Highlights: Progressive muscle loss is a predictor for worse survival in oral cavity cancer. Acute toxicities were not associated with muscle loss 9 months post-treatment. Patients who progressively lost muscle mass after treatment developed recurrence. Muscle mass of patients without recurrence returned to baseline during follow-up. Muscle loss is occult and may not be detected by body weight measurements. Abstract: Background and purpose: To investigate the association between progressive muscle loss and survival outcomes of patients with advanced-stage oral squamous cell carcinoma (OSCC) undergoing surgery and adjuvant (chemo)radiotherapy. Methods: We analyzed the computed tomography (CT) scans of 155 patients with stage III–IVB OSCC at baseline, at simulation CT for radiotherapy, and at 3- and 9-months post-treatment. Skeletal muscle index (SMI) was measured using CT at the C3 vertebral level. The predictors of overall survival (OS) and recurrence-free survival (RFS) were evaluated using Cox regression models. Results: The median follow-up period was 75.0 months. Fifty-one patients (32.9%) developed recurrence, with the median time from the fourth CT to recurrence being 9.1 months. The SMI progressively decreased from baseline to simulation CT by 1.1% ( p = 0.006), to 3 months post-treatment by 5.1% ( p < 0.001), and to 9 months post-treatment by 15.6% ( p < 0.001) in patients developing recurrence. Patients without recurrence lost SMI at the simulation CT by 0.7% ( p = 0.001) and at 3 months post-treatment by 2.1% ( p < 0.001); their SMI returned to the baseline level at 9 months post-treatment. SMI changes were weakly correlated with changes in body mass index (BMI) (Spearman ρ, 0.13; p = 0.11). In multivariate analysis, SMI changes (per 5% decrease) were independently associated with significantly worse OS (hazard ratio: 1.88, 95% confidence interval: 1.58–2.23; p < 0.001) and RFS (hazard ratio: 1.89, 95% confidence interval: 1.61–2.20; p < 0.001). Conclusion: Progressive muscle loss was independently associated with worse survival outcomes in patients with stage III–IVB OSCC. Muscle loss might not be detected by changes in BMI.